2022
DOI: 10.1029/2022gl097908
|View full text |Cite
|
Sign up to set email alerts
|

Fast Magnetosonic Waves in a Dipolarizing Flux Bundle Inside the Geosynchronous Orbit

Abstract: Although commonly observed in the inner magnetosphere, fast magnetosonic (MS) waves are often owe to be excited by those proton rings resulting from the so‐called energy‐dependent drift path of ring current protons. In this letter, we report an interesting MS wave event in a dipolarizing flux bundle (DFB) observed by the Van Allen Probe A. In the DFB, perpendicular proton fluxes are found depleted at low and intermediate energies, while enhanced at high energies, which should be attributed to proton accelerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
(73 reference statements)
0
4
0
Order By: Relevance
“…Recent studies have found that not only density structures but also magnetic structures can affect the wave propagations (e.g., Yu & Yuan, 2022). MS waves have also been observed locally in magnetic structures without any leakage (Yu et al., 2022), suggesting potential ducting effects of MS waves through full reflections by the magnetic structures. Our theoretical model might be able to include such ducting effects, for which some further improvements are needed to be performed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have found that not only density structures but also magnetic structures can affect the wave propagations (e.g., Yu & Yuan, 2022). MS waves have also been observed locally in magnetic structures without any leakage (Yu et al., 2022), suggesting potential ducting effects of MS waves through full reflections by the magnetic structures. Our theoretical model might be able to include such ducting effects, for which some further improvements are needed to be performed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…There are many factors involved in the formation of these magnetic field structures. In the inner magnetosphere, one of the most common ways to form magnetic peaks is magnetic compression due to sudden enhancements of the solar wind dynamic pressure (Xue et al., 2021), or the dipolarizing flux bundle (DFB) from the magnetotail (J. Liu et al., 2016; Yu et al., 2022). DFBs are the flux tubes with stronger B z than the background magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…These magnetic field structures are usually accompanied by dispersion of particle energies and pitch angles, resulting in complex and unstable particle distributions, which may provide free energy for wave excitation. Previous observations have shown that there are various types of plasma waves related to magnetic peaks, including kinetic Alfvén waves, lower hybrid drift waves, whistler waves, electron cyclotron waves, and MS waves (S. Y. Huang et al., 2012; Le Contel et al., 2009; Yu et al., 2022; Zhang & Angelopoulos, 2014; Zhou et al., 2009). These observed waves associated with magnetic structures belong to single instability (electron type or proton type), rarely taking into account waves driven by both proton and electron instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, magnetic structures, including magnetic dips and peaks, have often been found in the inner magnetosphere. Specifically, dipolarizing flux bundles (DFBs) carry particles and magnetic fields from the magnetotail into the inner magnetosphere during substorms (Birn et al., 2012; J. Liu et al., 2013; Runov et al., 2009; Sitnov et al., 2009) and often provide a magnetic field configured of magnetic peaks (J. Liu et al., 2016; Yu et al., 2022). Furthermore, the positive gradient portion of the DFBs, together with the intrinsic dipole magnetic field of the terrestrial magnetosphere (Artemyev et al., 2022; Gabrielse et al., 2016) or the negative gradient portion of the adjacent DFB (e.g., Malykhin et al., 2021; M. Zhou et al., 2009), form a magnetic dip in the radial direction.…”
Section: Introductionmentioning
confidence: 99%